2022
DOI: 10.1016/j.bioactmat.2021.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Controlled temperature-mediated curcumin release from magneto-thermal nanocarriers to kill bone tumors

Abstract: Systemic chemotherapy has lost its position to treat cancer over the past years mainly due to drug resistance, side effects, and limited survival ratio. Among a plethora of local drug delivery systems to solve this issue, the combinatorial strategy of chemo-hyperthermia has recently received attention. Herein we developed a magneto-thermal nanocarrier consisted of superparamagnetic iron oxide nanoparticles (SPIONs) coated by a blend formulation of a three-block copolymer Pluronic F127 and F68 on the oleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“… Physicochemical properties of iron oxide nanoparticles. (A) IONPs are used for MRI examination due to their good magnetic properties and biocompatibility ( Zhao et al, 2022 ); (B) IONPs are readily absorbed by cells and can label cells for cell tracking ( Iyer et al, 2017 ); (C) IONPs have magnetic heating properties and can substantially promote tumor cell death in vitro ( Iacoviță et al, 2021 ); (D) IONPs are used for targeted magnetic drug delivery ( Hola et al, 2015 ); (E) CSLM images showing MG-63 cancer cell line stained alive/dead at 41°C ( Khodaei et al, 2022 ); (F) IO-OA/PLGA produces mechanical stimulation in the presence of an external magnetic field and promotes osteogenic differentiation of MC3T3-E1 cells ( Hao et al, 2019 ). …”
Section: Iron Oxide Nanoparticles and Bone Regenerationmentioning
confidence: 99%
“… Physicochemical properties of iron oxide nanoparticles. (A) IONPs are used for MRI examination due to their good magnetic properties and biocompatibility ( Zhao et al, 2022 ); (B) IONPs are readily absorbed by cells and can label cells for cell tracking ( Iyer et al, 2017 ); (C) IONPs have magnetic heating properties and can substantially promote tumor cell death in vitro ( Iacoviță et al, 2021 ); (D) IONPs are used for targeted magnetic drug delivery ( Hola et al, 2015 ); (E) CSLM images showing MG-63 cancer cell line stained alive/dead at 41°C ( Khodaei et al, 2022 ); (F) IO-OA/PLGA produces mechanical stimulation in the presence of an external magnetic field and promotes osteogenic differentiation of MC3T3-E1 cells ( Hao et al, 2019 ). …”
Section: Iron Oxide Nanoparticles and Bone Regenerationmentioning
confidence: 99%
“…Studies have demonstrated that SIONs can effectively deliver cisplatin, curcumin, lauric acid, mitoxantrone, artemisinin, docetaxel, paclitaxel, dopamine, 10-hydroxycamptothecin, docetaxel, DOX, rifampicin, tetracycline hydrochloride, and other drugs ( Nagesh et al, 2016 ; Prakash et al, 2019 ; Vangijzegem et al, 2019 ). In addition, a few peptides, antibodies, or organic small molecules, such as amino-terminal fragment peptide ( Yang et al, 2009 ), anti-HER2/neu peptide ( Mu et al, 2015 ), anti-CD44 antibody ( Alsharif et al, 2020 ), prostate specific membrane antigen ( Bandini et al, 2017 ), β-cyclodextrin ( Sudha et al, 2016 ), and pluronic F127 polymer ( Khodaei et al, 2022 )were conjugated on the SION surfaces, consequently enhancing the targeting function of the SIONs delivery system, increasing the specificity and therapeutic effect.…”
Section: Classification Of Mnpsmentioning
confidence: 99%
“…In addition, studies have demonstrated that metal-based nanomaterials possess excellent mechanical properties as well as the intrinsic ability to significantly promote osseointegration, osteoconductivity, and osteoinduction, which has become crucial factors for bone regeneration (Sobolev et al, 2019;Eivazzadeh-Keihan et al, 2020a). Moreover, MNPs can help achieve the controlled release of drugs or active molecules through various stimuli responses, including pH-triggered release systems (Duan et al, 2021), redox reactions (Duan et al, 2018), external thermal effects (Khodaei et al, 2022), magnetic field control (Dehghani et al, 2020), and ultrasonic dynamic stimulation (Li S. et al, 2020), or by the external activation of optical/ mechanical stimuli (Feng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…TCP scaffolds are usually coated with synthetic biodegradable polymers, including polylactic glycolic acid 21–23 . However, degradation products of synthetic polymers could create toxicity and chronic inflammation, 24 and it is well accepted that natural origin materials hasten healing and provide greater biocompatibility with human tissues 25–27 . Therefore, researchers in the field of biomaterials have tried to find or develop any natural polymer that could be applied as a coating on a ceramic scaffold with toughening effects.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] However, degradation products of synthetic polymers could create toxicity and chronic inflammation, 24 and it is well accepted that natural origin materials hasten healing and provide greater biocompatibility with human tissues. [25][26][27] Therefore, researchers in the field of biomaterials have tried to find or develop any natural polymer that could be applied as a coating on a ceramic scaffold with toughening effects. Moreover, agarose is a natural polymer with extracellular matrix-like behavior.…”
Section: Introductionmentioning
confidence: 99%